Dynamics of silver photo-diffusion into Ge-chalcogenide films: time-resolved neutron reflectometry. (May 2015) - Sakaguchi, Y; Asaoka, H; Uozumi, Y; Kawakita, Y; Ito, T; Kubota, M; Yamazaki, D; Soyama, K; Ailavajhala, M; Latif, M R; Wolf, K; Mitkova, M; et al.
Abstract: Silver diffuses into an amorphous (a-) chalcogenide layer while visible light illuminates Ag/a-chalcogenide films and neutron reflectometry is a suitable technique probing time evolution of the depth profiles without damaging the sample by the probe beam itself. In this paper, we report the results of time-resolved neutron reflectivity measurements of a-Ge40 Se60 /Ag/ Si films taken while the films are exposed to visible light. From the measurements, we found enormous changes in the neutron reflectivity profile, including a loss of total reflection region, with continuous illumination even after forming one homogeneous layer, which occurred about 50 min after starting illumination. At this stage, a clear off-specular scattering was observed by a linear detector and a surface roughness was observed with naked eyes.